2011
DOI: 10.1111/j.1755-0238.2011.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic potential for viticulture in Central Chile

Abstract: Artículo de publicación ISIBackground and Aims: Central Chile represents a large area of viticultural potential for high-quality wine production. Although climate has been commonly accepted as one of the main drivers of Chilean viticultural success, its main features have not been described from a viticultural perspective. Our work focused on analysing the spatial climatic structure in this area with respect to the potential for grapevine production.CYTED of Ibero-Americ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…Lorenzo et al (2012) also reported that the Rías Baixas coastal region, one of the most productive viticultural regions in Spain, lies below an altitude of 300 m and has an Atlantic climate, with a mean annual temperature of about 15°C and an annual rainfall of about 1 600 mm. Montes et al (2012) reported that the Casablanca Valley in Chile, near the eastern edge of the Maipo, Cachapoal and Maule Valleys -the highest zones near the Andes, is classified as temperate according to the HI (HI 1988). Although the heliothermal potential of such locations limits the cultivation of red wine varieties such as Cabernet Sauvignon and Carménère, which have relatively high thermal requirements, they can be suitable for early-ripening varieties such as Pinot Noir and Riesling.…”
Section: Phenological Events For the Study Area: 2010 To 2011mentioning
confidence: 99%
“…Lorenzo et al (2012) also reported that the Rías Baixas coastal region, one of the most productive viticultural regions in Spain, lies below an altitude of 300 m and has an Atlantic climate, with a mean annual temperature of about 15°C and an annual rainfall of about 1 600 mm. Montes et al (2012) reported that the Casablanca Valley in Chile, near the eastern edge of the Maipo, Cachapoal and Maule Valleys -the highest zones near the Andes, is classified as temperate according to the HI (HI 1988). Although the heliothermal potential of such locations limits the cultivation of red wine varieties such as Cabernet Sauvignon and Carménère, which have relatively high thermal requirements, they can be suitable for early-ripening varieties such as Pinot Noir and Riesling.…”
Section: Phenological Events For the Study Area: 2010 To 2011mentioning
confidence: 99%
“…The study lasted three seasons (2004-2005, 2005-2006, and 2006-2007) and was conducted in a drip-irrigated vineyard (Vitis vinifera L.) with own-rooted 'Carménère' vines established in 1997; vine spacing between rows was 2.5 m and vine spacing within the row 1.5 m. The zone has a sub-humid Mediterranean climate with a mean maximum temperature of 32 ºC in January, an annual mean of 14 ºC, and annual mean rainfall of 564 mm with a standard deviation of 236 mm, with 92% annual amounts during May to September for the period 1960 to 2006 (Arumí et al, 2013). There is high heat accumulation (heliothermal index, HI = 2441), which is a suitable condition for 'Carménère' (Montes et al, 2012). The soil is Typic Xerochrepts, alluvial origin, surface slope about 0.4% to the south, with a clay loam texture at the surface that varies to sandy loam at 1.0 m depth, and coarse sand, gravel and stone at depths greater than 1 m; soil bulk density 1.66 Mg m Figure 1 shows a field layout of the general condition of the Peumo area and the site of experiment.…”
Section: General Background Of the Study Areamentioning
confidence: 99%
“…Four bioclimatic indices commonly used in grapevine-related studies (Tonietto and Carbonneau, 2004 ;Hall and Jones, 2010 ;Montes et al, 2012) are determined : the average Growing Season Temperature (GST), the Growing DegreeDays Index (GDDI), the Huglin's Heliothermal Index (HI) and the Cool Night Index (CNI). They are calculated over the entire growing season, from October to April, as described below, except the HI which is calculated from October to March.…”
Section: Bioclimatic Indicesmentioning
confidence: 99%